Live, Love, and Suffer: The Lived Experiences of Trans Women Parents with Children in Cebu - Bacus, Hans; Herames , Christine Silvery; Solibaga , Sean Joseph; Villamor, Roque Luis Manuel; Cimafranca , John Stephen; Talens, Diana Marie; Maghanoy, Sarah Jean; Gagani, Flordeliza (Future Science / FSH-PH Publications, 2024)
Parenthood entails daunting responsibilities, even more so if parents are of a different gender spectrum such as trans women. Against a rigid heteronormative society, this phenomenological study explored the challenges and the struggles, as well as the coping mechanisms, of the trans-women parents in Metro Cebu, Philippines. Through Husserlian’s descriptive phenomenology, five participants were chosen through snowball sampling to share their experiences through in-depth interviews in 2023. Utilizing Colaizzi’s method of data analysis, the study revealed seven (7) recurring themes: (1) Financial Instability; (2) Societal Acceptance; (3) Shifting Family Dynamics; (4) Lack of Legal Government Protection; (5) Employment Possibilities; (6) Perseverance; and (7) Communication. These findings provided insights into the lives of trans-women parents in the Philippines and offered recommendations for policies that could help address the issues faced by this sub-group of parents. Moreover, this study served as a contribution to the literature on non-heteronormative families through the lived experiences of trans-women parents in a heteronormative society like the Philippines.